Managerial economics in a global economy - Salvatore, Dominick (New York, N.Y. Oxford University Press, 2015)
"Reflecting the highly globalized nature of tastes, production, labor markets, and financial markets in today's world, Managerial Economics in a Global Economy, Eighth Edition, presents the theory of the firm as a unifying theme to examine the managerial decision-making process. Adopting a global perspective, it synthesizes economic theory, decision science, and business administration studies, examining how they interact as a firm strives to reach optimal profitability and efficiency in the face of modern constraints. Features * Integrates examples, data, and theories on the international ramifications of managerial decisions into the entire text, rather than segregating the material in a separate chapter * Incorporates 127 case studies, showing how firms actually reach managerial decisions today * Offers instructors maximum flexibility with a modular structure that is suitable for both full-term and briefer courses, and can be used with or without calculus * Includes a robust instructor ancillary package for adopters"--Provided by publisher.
"Managerial Economics in a Global Economy, Eight Edition, synthesizes economic theory, decision science, and business administration studies, examining how they interact as a firm strives to reach optimal profitability and efficiency in the face of modern constraints"--Provided by publisher.
PART ONE INTRODUCTION -- CHAPTER 1 The Nature and Scope of Managerial Economics -- CHAPTER 2 Demand, Supply, and Equilibrium Analysis -- CHAPTER 3 Optimization Techniques and New Management Tools -- PART TWO DEMAND ANALYSIS -- CHAPTER 4 Demand Theory -- CHAPTER 5 Demand Estimation -- CHAPTER 6 Demand Forecasting -- PART THREE PRODUCTION AND COST ANALYSIS -- CHAPTER 7 Production Theory and Estimation -- CHAPTER 8 Cost Theory and Estimation -- PART FOUR MARKET STRUCTURE AND PRICING PRACTICES -- CHAPTER 9 Market Structure: Perfect Competition, Monopoly, and Monopolistic Competition -- CHAPTER 10 Oligopoly and Firm Architecture -- CHAPTER 11 Game Theory and Strategic Behavior -- CHAPTER 12 Pricing Practices -- PART FIVE REGULATION, RISK ANALYSIS, AND CAPITAL BUDGETING -- CHAPTER 13 Regulation and Antitrust: The Role of Government in the Economy -- CHAPTER 14 Risk Analysis -- CHAPTER 15 Long-Run Investment Decisions: Capital Budgeting.
Photocopy.
Includes bibliographical references and index.
Keywords: Managerial economics